THE LOCATION OF EDUCATIONAL INSTITUTIONS AS A FACTOR OF SOCIAL REALIZATION OF THE RIGHT TO EDUCATION IN THE REPUBLICS OF THE NORTH-CAUCASUS FEDERAL DISTRICT OF THE RUSSIAN FEDERATION AND THE REPUBLIC OF SOUTH OSSETIA - E. Tereshchenko; D. Zaseev (Гуманитарные и юридические исследования)
The aim of the study is the formation of knowledge about the state and guarantee of the human right to education to develop recommendations for use in the actual integration of educational spaces of the Russian Federation and the Republic of South Ossetia. The legislation on education is constantly striving for improvement. New legal mechanisms to regulate the sphere of education are used. In the recent history of the Russian Federation, a new law on education was adopted in 2012, in South Ossetia, laws were adopted in 2008 and 2017. To some extent, the application of legislative acts should be ad- justed by making changes to them or by adopting acts of subordinate nature. The article presents a comparative analysis of the actual degree of guarantee of the right to education in the Republic of South Ossetia and the North-Caucasus republics of the Russian Federation, whose educational complexes are most closely correlated with the educational complex of South Os-setia. The article summarizes the law enforcement practice on the protection of children's rights to education. Social risks that significantly affect the realization of the human right to education in Russia and South Ossetia are identified. First, the emphasis is placed on the physical realization of the right to education, which depends on the territorial organization of the system of educational institutions. The lack of places in general education institutions entails their overcrowding, violation of sanitary norms and rules of the educational process. The enrollment system requires both regulatory improvement and information transparency. A promising area of availability of pre-school education services is the development of variable forms of work with children who do not attend pre-school educational institutions. To this end, work is needed to encourage and assist citizens in opening private pre-school institutions. Based on the analysis of social factors affecting the realization of the rights and freedoms of the individual, in the future it is possible to formulate legal mechanisms, neutralizing the negative impact of these factors on the degree of actual implementation of human rights, as well as to facilitate the proper adjustment of the existing legislation of Russia and South Ossetia on education.